A MUSE View of the HDFS: The Lyα Luminosity Function out to z~6. Issue Volume 11:Issue S319(2015) (17th August 2016) - Drake, Alyssa B.; Guiderdoni, Bruno; Blaizot, Jérémy; Richard, Johan; Bacon, Roland; Garel, Thibault; Hashimoto, Takuya; ,
Abstract: We present preliminary results from MUSE on the Lyα luminosity function in the Hubble Deep Field South (HDFS). Using a large homogeneous sample of LAEs selected through blind spectroscopy, we utilise the unprecedented detection power of MUSE to study the progenitors of L* galaxies back to when the Universe was just ~2 Gyr old. We present these results in the context of the current literature, and highlight the importance of the forthcoming Hubble Ultra Deep Field (HUDF) study with MUSE, which will increase the size of our sample by a factor of ~ 10.